2014
DOI: 10.3233/ch-121659
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the hematocrit and slow coronary flow

Abstract: BACKGROUND: Whether the hematocrit is implicated in the pathogenesis of slow coronary flow (SCF) is not known. METHODS: To evaluate the correlation between the hematocrit and SCF, we studied 367 patients with angiographically near-normal coronary arteries. They were divided into four quartiles based on the hematocrit. The corrected thrombolysis in myocardial infarction frame count (TFC) was used to document velocity of coronary flow. RESULTS: From the first through to the fourth quartile, the percentage of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Numerous factors contribute to microvascular and circulatory dysfunction, including coronary microvascular imbalance and increased tonus, endothelial thickening of small vessels and endothelial nitric oxide imbalance, and blood viscosity. Hb concentration is a determinant of blood viscosity, and a significant relationship between CSF and Hb concentration has been demonstrated previously [ 11 ]. The SCF patients frequently present with elevated blood viscosity [ 23 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous factors contribute to microvascular and circulatory dysfunction, including coronary microvascular imbalance and increased tonus, endothelial thickening of small vessels and endothelial nitric oxide imbalance, and blood viscosity. Hb concentration is a determinant of blood viscosity, and a significant relationship between CSF and Hb concentration has been demonstrated previously [ 11 ]. The SCF patients frequently present with elevated blood viscosity [ 23 ].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, PDW has also been linked to saphenous vein graft patency among patients who underwent coronary artery bypass [ 10 ]. Haemoglobin (Hb) is a key determinant of blood viscosity [ 11 ]. Red cell distribution width (RDW) is a direct measure of the variation in erythrocyte size that is easily measured as a component of routine blood counts [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms behind the hemoglobin-associated thrombotic risks have been proposed, including reduced coronary and cerebral blood flow as well as enhanced exposure of platelets and coagulation factors to the vascular endothelium resulting in increased platelet-vessel wall adhesion. [5,12,[22][23][24] Whether these changes can be reversed by lowering the hemoglobin concentration through phlebotomy remains to be elucidated. Individuals included in our study donated blood in volumes equivalent to phlebotomies, however, as blood donors are only allowed to donate whole blood a maximum of three and four times per year for men and women, respectively, and in reality only donated an average of 1.6 and 1.9 times per year, we argue that their donation habits are unlikely to have had large therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the studies directly suggested a positive association between Hct and serum uric acid 33 34 35 , some other researches indicated a positive trend between Hct and serum uric acid in a variety of settings, such as screen-based cohorts 42 43 , subjects with intact kidney function in community-based cohorts 44 , screen-based cross-sectional survey 45 , slightly reduced glomerular filtration rate 46 , and angiographically near normal coronary arteries 47 , even though the significance of difference remained unclear. The present study was the first one demonstrating that higher Hct level at baseline is associated with an increased risk of HU during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%